2022
DOI: 10.1093/hmg/ddac055
|View full text |Cite
|
Sign up to set email alerts
|

CAMLG-CDG: a novel congenital disorder of glycosylation linked to defective membrane trafficking

Abstract: The transmembrane domain recognition complex (TRC) pathway is required for the insertion of C-terminal tail-anchored (TA) proteins into the lipid bilayer of specific intracellular organelles such as the endoplasmic reticulum (ER) membrane. In order to facilitate correct insertion, the recognition complex (consisting of BAG6, GET4 and UBL4A) must first bind to TA proteins and then to GET3 (TRC40, ASNA1) which chaperones the protein to the ER membrane. Subsequently, GET1 (WRB) and CAML form a receptor which enab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
3
10
0
Order By: Relevance
“…Among the latter were 3 TA membrane proteins (GOLGA5, UBE2J2, and the peroxisomal FAR1), 2 single-spanning membrane proteins, 8 multi-spanning membrane proteins, and the ER hairpin protein REEP3 ( Figure 2 A, Tables S4 and S5 ). Of these 27 negatively affected proteins, 13 are N-glycosylated (including 11 proteins with SP), which is consistent with the reports that pathogenic variants of Caml as well as TRC35 or TRC40 are linked to congenital disorders of glycosylation in human patients [ 57 ]. Thus, similar to SRP/SR, 48% of the observed Wrb clients have N-terminal SP, and 57% (i.e., 8 out of a total of 14) of the remaining membrane protein clients have more C-terminal TMHs ( Tables S4 and S5 ).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Among the latter were 3 TA membrane proteins (GOLGA5, UBE2J2, and the peroxisomal FAR1), 2 single-spanning membrane proteins, 8 multi-spanning membrane proteins, and the ER hairpin protein REEP3 ( Figure 2 A, Tables S4 and S5 ). Of these 27 negatively affected proteins, 13 are N-glycosylated (including 11 proteins with SP), which is consistent with the reports that pathogenic variants of Caml as well as TRC35 or TRC40 are linked to congenital disorders of glycosylation in human patients [ 57 ]. Thus, similar to SRP/SR, 48% of the observed Wrb clients have N-terminal SP, and 57% (i.e., 8 out of a total of 14) of the remaining membrane protein clients have more C-terminal TMHs ( Tables S4 and S5 ).…”
Section: Resultssupporting
confidence: 87%
“…Unexpectedly, however, we identified many more Wrb as well as Wrb and hSnd2 clients than just TA proteins, including proteins with relatively central and even N-terminal TMHs ( Figure 2 A,G). These findings may point towards both a more general targeting role of the TRC pathway than previously anticipated and a contribution to the congenital disorders of glycosylation in human patients with pathogenic variants of Caml, TRC35, or TRC40 [ 57 ]. Together with previous observations that small human presecretory proteins can be targeted to the ER of semi-permeabilized human cells by SRα, Wrb, and hSnd2 [ 29 , 33 ] and that the cytosolic quality control and TRC pathway component SGTA is cotranslationally recruited to ribosomes, which synthesize a diverse range of membrane proteins, including those with cleavable SP [ 58 ], the possibility of a more general role of the TRC pathway in ER targeting undoubtedly warrants future study.…”
Section: Discussionmentioning
confidence: 99%
“…However, when more WRB clients were identified under conditions of simultaneous depletion of WRB and hSnd2 (Figure 6) a preference of WRB for multispanning membrane proteins became visible and more WRB membrane protein clients were observed to have relatively more central and more carboxy-terminal TMH as compared to SRA dependent membrane proteins (Tirincsi et al, 2022b). Taken together, these results on the client spectrum of WRB point towards a more general targeting role of the TRC pathway than previously anticipated and may explain why pathogenic variants of TRC35 or TRC40 as well as CAML are linked to Congenital disorders of glycosylation in humans (Wilson et al, 2022). Notably, first hints towards this end already came from previous reports that small human presecretory proteins can be targeted to the ER of semi-permeabilized human cells by SR, WRB and hSnd2 (Haßdenteufel et al, 2018;Haßdenteufel et al, 2019) and that the cytosolic TRC pathway-component SGTA, which works upstream of Bag6, Ubl4A, and TRC35, is cotranslationally recruited to ribosomes, which synthesize a diverse range of membrane proteins, including those with cleavable SP (Leznicki and High, 2020).…”
Section: Trcmentioning
confidence: 71%
“…Furthermore, ERj1 was found to be subject to phosphorylation ( Götz et al, 2009 ) and TRAPα was found to be subject to phosphorylation as well as Ca 2+ -binding ( Wada et al, 1991 ) and, therefore, may reciprocally respond to the same cellular conditions as compared to Sec62/Sec63. We are convinced that the detected variations in SP and TMH characteristics are responsible for the known precursor specific defects in various human diseases, termed Sec61-channelopathies (reviewed by Haßdenteufel et al, 2014 ; Sicking et al, 2021a ), which include SEC61A1 -linked Common variable immunodeficiency ( Schubert et al, 2018 ), Neutropenia ( Van Nieuwenhove et al, 2020 ) and Tubulointerstitial kidney disease ( Bolar et al, 2016 ; Sicking et al, 2022 ), SEC61B - and SEC63 -linked Polycystic liver disease ( Fedeles et al, 2011 ; Lang et al, 2012 ; Besse et al, 2017 ), and SSR - as well as CAML -linked Congenital disorders of glycosylation ( Pfeffer et al, 2017 ; Nguyen et al, 2018 ; Wilson et al, 2022 ) ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mammalian homolog ASNA1 not only plays an essential role in tail-anchored (TA) protein insertion (Colombo et al, 2016) and insulin secretion (Norlin et al, 2017) but has been characterized as an important biomarker in treatment response in schizophrenia (Mamdani et al, 2013), predicting disease severity of dengue virus infection (Soe et al, 2018), differentiation between subjects with active and latent tuberculosis (Mistry et al, 2007), a biomarker for abnormalities associated with ultra-high-risk for psychosis (Zhang et al, 2020), as well as a biomarker for Down's syndrome (Sui et al, 2015). Mutations in ASNA1 are associated with pediatric cardiomyopathy (Verhagen et al, 2019) and mutations in its pathway protein CAML are linked in patients to hypotonia, brain abnormalities, and epilepsy (Wilson et al, 2022). Further ASNA1 interacts with and likely modulates the function of VAPB which is mutated in cases of amyotrophic lateral sclerosis (Baron et al, 2014).…”
Section: Introductionmentioning
confidence: 99%